CIGARETTE COMPANY'S RESPONSIBILITY FOR CONSUMER HEALTH LOSSES AFTER HEALTH WARNING INCLUSION - Setiawan, Ginanjar Adi; Hasanah, Uswatun (Faculty of Law Universitas Trunojoyo Madura, 2020)
This study aims to examine whether cigarette companies can release responsibility for the health losses of smokers by including warnings on the dangers of smoking on cigarette packages and analyze how responsibility can be imposed on cigarette companies for the health losses of smokers. This research is a normative juridical study with a statute approach. The primary and secondary legal materials obtained are systematized and synchronized through deductive logic, then analysis is carried out using the interpretive method to provide answers to the proposed legal problems. The results show that cigarette business actors can release responsibility for the health losses of consumers due to smoking if the health losses are as stated in the warning of the dangers of smoking on cigarette packages. However, cigarette companies that cause consumer health losses beyond what is stated in the warning of the dangers of smoking contained in cigarette packs, can be liable based on the principle of product responsibility with a variety of the presumption of always being responsible.